2007
DOI: 10.1080/01919510701459550
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ozone for Disinfection and Taste and Odor Control at Proposed Membrane Facility

Abstract: Zone 7 of Alameda County Flood Control and WaterConservation District, in coordination with Black & Veatch, conducted a 9-month pilot study to determine preliminary design parameters for a new water treatment plant (WTP). The pilot study was performed to verify the performance of membrane filters and to establish preliminary design parameters for the submerged membrane process, followed by ozonation and biological granular activated carbon filtration. The pilot testing was conducted using water from the Patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The oxidative reaction is very quick. Generally, the concentration of residual ozone is halved in the first 30 ​s [ [26] , [27] , [28] ] and reaches at least a 1-log inactivation [ 29 ]. It is reported that oxidation of proteins by ozone mainly occurs at the tyrosine, tryptophan, histidine, cysteine, and methionine residues, resulting in the abnormal folding ability and changed higher order structures [ 30 ].…”
Section: The Virus Removal By Ozonationmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxidative reaction is very quick. Generally, the concentration of residual ozone is halved in the first 30 ​s [ [26] , [27] , [28] ] and reaches at least a 1-log inactivation [ 29 ]. It is reported that oxidation of proteins by ozone mainly occurs at the tyrosine, tryptophan, histidine, cysteine, and methionine residues, resulting in the abnormal folding ability and changed higher order structures [ 30 ].…”
Section: The Virus Removal By Ozonationmentioning
confidence: 99%
“…High temperature reduces the solubility of ozone in water, accelerates the decomposition of ozone but also the disinfection process. In common temperature range between 5 and 30 ​°C, a rise in temperature increases the efficiency of ozone disinfection and decreases the CT value [ 25 , 26 , 36 ]. The temperature coefficient is applied to describe the fold reduction of CT values induced by a 10 ​°C decrease.…”
Section: The Virus Removal By Ozonationmentioning
confidence: 99%
See 1 more Smart Citation
“…In some applications ozone is preferred because of its minor odour effect at low concentrations, its colour and taste absence and its effective viral inactivation potential [13,14]. But above all ozone appear an excellent microbicide, because good sanitary efficiencies are obtained with small doses of ozone and short treatment application time [15].…”
Section: Ozone Disinfection Treatment In Swimming Poolsmentioning
confidence: 99%
“…A typical ozone application is for odor control (Edwards-Brandt et al 2007), specifically the removal of hydrogen sulfide from well water for odor control (Duranceau et al 2010). Hydrogen sulfide (H 2 S) is oxidized rapidly with ozone to form sulfate.…”
Section: Introductionmentioning
confidence: 99%